Mustilia (Smerkata) zolotuhini, a new species (Lepidoptera: Endromidae) from China - Saldaitis, Aidas; Ivinskis, Povilas; Rimsaite, Jolanta (Zootaxa, 2015)
The genus Mustilia Walker subgenus Smerkata Zolotuhin 2007 was revised by Zolotuhin (2007) to include seven species from the South–Palearctic to Oriental regions: (Mustilia (Smerkata) phaeopera Hampson (type species), Mustilia (Smerkata) fusca Kishida, Mustilia (Smerkata) craptalis Zolotuhin, Mustilia (Smerkata) soosi Zolotuhin, Mustilia (Smerkata) brechlini Zolotuhin, Mustilia (Smerkata) tzarica Zolotuhin, and Mustilia (Smerkata) ulliae Zolotuhin. An unanticipated discovery of a new species from Sichuan Province, China adds an eighth species to this subgenus.